2013
DOI: 10.2131/jts.38.193
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent regional brain acetylcholinesterase and acylpeptide hydrolase inhibition without cell death after chlorpyrifos administration

Abstract: -Organophosphates (OPs) are important toxic compounds commonly used for a variety of purposes in agriculture, industry and household settings. It has been well established that the main mechanism of acute toxic action of OP is the inhibition of acetylcholinesterase (AChE). However, we observed long term deficit after acute subcutaneous exposure to Chlorpyrifos (CPF) even when AChE activity is restored. In fact, besides AChE inhibition, non-AChE targets have also been proposed as an alternative mechanism involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 82 publications
(108 reference statements)
0
9
0
1
Order By: Relevance
“…It is located in the synaptic region (Sandoval et al, 2012) and its inhibition by dichlorvos has been demonstrated to enhance long term potentiation in hippocampal slices (Olmos et al, 2009). While exposure to CPF results in higher levels of ChE inhibition than APH inhibition in the early periods following exposure, the inhibition of APH is much more persistent than is that of AChE (Quistad et al, 2005; Cardona et al, 2013; Lopez-Granero et al, 2013a). However, subsequent long term behavioral studies involving either a high dose acute exposure or a chronic feeding exposure to CPF did not find any association between APH activity and cognitive deficits observed (Lopez-Granero et al, 2013b; 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is located in the synaptic region (Sandoval et al, 2012) and its inhibition by dichlorvos has been demonstrated to enhance long term potentiation in hippocampal slices (Olmos et al, 2009). While exposure to CPF results in higher levels of ChE inhibition than APH inhibition in the early periods following exposure, the inhibition of APH is much more persistent than is that of AChE (Quistad et al, 2005; Cardona et al, 2013; Lopez-Granero et al, 2013a). However, subsequent long term behavioral studies involving either a high dose acute exposure or a chronic feeding exposure to CPF did not find any association between APH activity and cognitive deficits observed (Lopez-Granero et al, 2013b; 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CPF and Cd have very different modes of action in the organisms. CPF inhibits the activity of acetylcholinesterase 25,26 . Cd causes the nephrotoxicity in the body 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more attention needs to be given to the combined toxicity of CPF and Cd. CPF mainly inhibited the activity of acetylcholinesterase (Reiss et al, 2012;Cardona et al, 2013). Cd accumulated in the body and led to the nephrotoxicity (Johri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%